Reshaping Islamic Knowledge, Advocating Wasaṭism: The Azharites and the Transformation of Urban Religious Learning in Banda Aceh, Indonesia - Ichwan, Moch. Nur; Shadiqin, Sehat Ihsan; Mujtahid, Mujtahid (Ulumuna, 2025)
This article examines the significant role of the Azharites (Al-Azhar alumni) in reshaping Islamic knowledge alongside the transformation of urban religious learning in Banda Aceh over the past two decades. The study highlights their contributions to disseminating Islamic knowledge through platforms like the Middle East Alumni Association (Ikatan Alumni Timur Tengah—IKAT), advanced reading communities, mosques, coffee shops, and mass/social media. They have facilitated public learning in classical Islamic knowledge, such as tafsīr, taḥsin al-Qur’an, ḥadīth, fiqh, uṣūl al-fiqh, ʿaqīdah, sīrah, and mawārith by introducing not only basic and intermediate but also advanced religious texts. Furthermore, the Azharites have promoted also Wasaṭism (wasaṭiyyah, moderation) in the understanding of Islam, rooted in Shafi'ite-Ash'arite traditions, while incorporating texts from other madhhabs, such as the Hanafite, Hanbalite, and Malikite schools, in comparative way. Their approach distinguishes them from both the strict madhhabism and the anti-madhhabism of Salafi-Wahhabism and radical Islamism. The study concludes that the Azharites have contributed to the discursive democratization and reform, which have resulted in the reshaping of Islamic knowledge in Banda Aceh—and Aceh province in general—and the moderation of madhhabism, by introducing Wasaṭism and fostering alternative urban religious learning.